RF Based Sign Board Detection and Collision Avoidance System - Nayak, Ravikiran; Chandra, Dilip (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2017)
Nowadays the percentage of accidents has been going up day by day. This might be because of driver negligence of not following the traffic rules and sign boards. RF based sign board detection and collision avoidance system is such approach where the rider of the vehicle will get advance intimation of fore coming hurdles. Also, it detects front vehicle distance. This system is very helpful in cloudy area, curved roads. At night it is very difficult for driver to see the sign boards, answer for these issues is the ‘RF based sign board detection and collision avoidance system.